Persistence of the Short Story in Sergio Ramírez - Burgos Pérez, Fernando (2016)
This study discusses, in the first place, the artistic factors expounding the innovative contribution of the short story production by Sergio Ramírez in Latin America. The second part of this study is a sociocultural analysis of the story “Charles Atlas also dies” focusing on his critique of the commodification of the human body. This approach involves elucidating the artistic function of historical components and sociocultural fetishes as well as the fraudulent networks generated by the manipulations of the symbols of capital and its spectral becoming.